Contemporary UK paramedical training and education. How do we train? How should we educate?. Issue 5 (20th April 2005) - Cooper, S
Abstract : Objective: To develop an understanding of the current system and future development of training and education within a large UK ambulance trust, based upon the experiences, beliefs, and opinions of stakeholders. Methods: This was a qualitative naturalistic inquiry using an interpretative constructivist approach for 44 interviews with a range of ambulance staff. Stakeholder views on training and education were analysed and compared using the constant comparison method. Results: Key emergent themes included: issues around prescribed programme entry levels and methods; the desire for a higher education curriculum with a balance between theory and practice; valid and reliable assessment methods; development of a supportive mentorship framework; an emphasis on self directed professional development with a focus on deskilling issues; and development of interprofessional collaborative links. Conclusion: This thematic review suggests that this UK ambulance service is in a transition stage, with significant organisational, professional, and cultural challenges. The dichotomies, boundaries, and development issues are part of the development of an emerging profession for which it is essential that the educational agenda is addressed.